Isoform‐Specific SCFFbw7 Ubiquitination Mediates Differential Regulation of PGC‐1α. Issue 4 (April 2015) - Trausch‐Azar, Julie S.; Abed, Mona; Orian, Amir; Schwartz, Alan L.
<x xml:space="preserve">Abstract</x> The E3 ubiquitin ligase and tumor suppressor SCFFbw7 exists as three isoforms that govern the degradation of a host of critical cell regulators, including c‐Myc, cyclin E, and PGC‐1α. Peroxisome proliferator activated receptor‐gamma coactivator 1α (PGC‐1α) is a transcriptional coactivator with broad effects on cellular energy metabolism. Cellular PGC‐1α levels are tightly controlled in a dynamic state by the balance of synthesis and rapid degradation via the ubiquitin‐proteasome system. Isoform‐specific functions of SCFFbw7 are yet to be determined. Here, we show that the E3 ubiquitin ligase, SCFFbw7, regulates cellular PGC‐1α levels via two independent, isoform‐specific, mechanisms. The cytoplasmic isoform (SCFFbw7β) reduces cellular PGC‐1α levels via accelerated ubiquitin‐proteasome degradation. In contrast, the nuclear isoform (SCFFbw7α) increases cellular PGC‐1α levels and protein stability via inhibition of ubiquitin‐proteasomal degradation. When nuclear Fbw7α proteins are redirected to the cytoplasm, cellular PGC‐1α protein levels are reduced through accelerated ubiquitin‐proteasomal degradation. We find that SCFFbw7β catalyzes high molecular weight PGC‐1α‐ubiquitin conjugation, whereas SCFFbw7α produces low molecular weight PGC‐1α‐ubiquitin conjugates that are not effective degradation signals. Thus, selective ubiquitination by specific Fbw7 isoforms represents a novel mechanism that tightly regulates cellular PGC‐1α levels. Fbw7 isoforms mediate degradation of a host of regulatory proteins. The E3 ubiquitin ligase, Fbw7, mediates PGC‐1α levels via selective isoform‐specific ubiquitination. Fbw7β reduces cellular PGC‐1α via ubiquitin‐mediated degradation, whereas Fbw7α increases cellular PGC‐1α via ubiquitin‐mediated stabilization. J. Cell. Physiol. 230: 842–852, 2015. © 2014 Wiley Periodicals, Inc.